Risky Behavior And The Precautions Of HIV / AIDS Trasnmission On Fisherman Community Of Nine Islands - Andi Nurlaela Amin; Sudirman (Comprehensive Health Care, 2020)
The development of new cases of HIV in Indonesia increased significantly in 2013 and 2014, respectively by 29,037 and 32,711 cases. The results of the risky behavior survey (1996-2000) showed that truck drivers, sailors and fishermen and other port workers including workers which are often mobile (mobile population), are vulnerable to HIV because of their sexual behavior and the nature of their work. Sinjai District is one of the districts with a considerable population of fishermen (8,544 fishermen) in South Sulawesi. This research aims to analyze the relationship between level of knowledge with risky behavior and the precautions of HIV / AIDS transmission on fishermen in Sinjai District in 2016. Method of this research is an analytical research with cross sectional study approach. Population were the fisherman who registered in zero survey of Public Health Service of Sinjai District with 40 samples taken by simple random sampling. Data analysis uses statistical test of chi square. The research results showed that 72.5% of fishermen did not know about HIV / AIDS transmission, 75% had risky behavior, and 65% did not take the precautions of HIV / AIDS transmission. Chi square test results showed that there is no significant relationship between level of knowledge about HIV / AIDS transmission with risky behavior of fishermen (p count, 0,152 > p value 0,05). While there is a significant relationship between the level of knowledge with the precautions of HIV / AIDS transmission (p count, 0.034 < p value, 0.05).